The structure of Serratia marcescens Lip, a membrane-bound component of the type VI secretion system - Rao, Vincenzo A. (International Union of Crystallography, 2011)
Lip is a membrane-bound lipoprotein and a core component of the type VI secretion system found in Gram-negative bacteria. The structure of a Lip construct (residues 29–176) from Serratia marcescens (SmLip) has been determined at 1.92 Å resolution. Experimental phases were derived using a single-wavelength anomalous dispersion approach on a sample cocrystallized with iodide. The membrane localization of the native protein was confirmed. The structure is that of the globular domain lacking only the lipoprotein signal peptide and the lipidated N-terminus of the mature protein. The protein fold is dominated by an eight-stranded β-sandwich and identifies SmLip as a new member of the transthyretin family of proteins. Transthyretin and the only other member of the family fold, 5-hydroxyisourate hydrolase, form homotetramers important for their function. The asymmetric unit of SmLip is a tetramer with 222 symmetry, but the assembly is distinct from that previously noted for the transthyretin protein family. However, structural comparisons and bacterial two-hybrid data suggest that the SmLip tetramer is not relevant to its role as a core component of the type VI secretion system, but rather reflects a propensity for SmLip to participate in protein–protein interactions. A relatively low level of sequence conservation amongst Lip homologues is noted and is restricted to parts of the structure that might be involved in interactions with physiological partners.